Surface changes of orthodontic brackets following treatment with fixed orthodontic appliances (Mustansiria Dental Journal, 2018)
Fixed orthodontic appliances were used for long period in the treatment of malocclusion patients. It is subjected to the oral environment and affected by the changes that take place in this media. Many studies were done and express the tendency of these appliances to corrode inside the mouth. 150 orthodontic brackets related to three different companies (Orthodent, Ortho-organizers, and Dentaurum). These brackets examined after removing them from the patients' mouth and examined microscopically. Most of the brackets exhibit corrosion which is mainly pitting, crevice and erosion corrosion. Keywords: surface changes of orthodontic brackets